1972
DOI: 10.1302/0301-620x.54b4.723
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Trabecular Fatigue Fractures in the Femoral Head

Abstract: 1. The femoral head has been examined in specimens taken from cadavers, patients suffering subcapital fracture of the femoral neck and patients undergoing total replacement arthroplasty for osteoarthrosis and rheumatoid arthritis. 2. Lesions have been seen, some of which appear to be uniting fatigue fractures of individual trabeculae. 3. It is suggested that excessive cyclical loading, sometimes leading to fatigue fractures, may represent a fundamental pathological process of general importance in the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…The sclerotic changes varied in depth from 500 to 3,000 µ but were often abruptly bordered by spongy bone of normal appearance. No microscopic fractures or nodular aggregates (''birds nests'') (Todd et al, 1972) were found in this spongy bone. Mostly the trabeculae were highly mineralized without appreciable signs of remodeling of the bone.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 78%
“…The sclerotic changes varied in depth from 500 to 3,000 µ but were often abruptly bordered by spongy bone of normal appearance. No microscopic fractures or nodular aggregates (''birds nests'') (Todd et al, 1972) were found in this spongy bone. Mostly the trabeculae were highly mineralized without appreciable signs of remodeling of the bone.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 78%
“…This situation is not conducive to elasticity and support of the subchondral bone. Todd et al [19] showed that isolated trabecular fractures occur as a result of fatigue in the osteoporotic proximal femur and that this contributes to major fractures. Microfractures in the femoral head cause local collapse and result in incompatibility in cartilage, leading to OA.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of OA and OP in the hand joints has been previously shown. [9,19,20] Schneider et al [21] determined that female patients with clinically diagnosed hand OA had significantly lower femoral BMD, and Sowers et al [22] found that after a 23-year follow-up, the initial bone mass was higher in female patients who subsequently developed hand OA than those who did not. However, over time, a greater loss of bone was observed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic loading energies are probably distributed askew around a median value (normal locomotion), but loading energies between the median and the extreme (clinical fracture) are expected to occur more frequently than the extreme itself. Consequently, a relatively large number of subclinical fractures should occur (microfractures, trabecular fractures with preserved structure), which in fact they do (4,14,20,21). Another possibility is that energies as large as those involved with pore collapse could be local phenomena in the weaker fracturing part of the bone, and the average loading energy of a larger bone mass around the fracture site may not differ so much from energies involved with normal locomotion, e.g., an elderly woman losing her balance and sustaining a fracture of the lateral tibial condyle.…”
Section: Discussionmentioning
confidence: 99%